Prognostic value of matrix metalloproteinases and transforming growth factor – β in kidney cancer - A. I. Tarasenko; A. N. Rossolovskiy; O. L. Berezinets; A. B. Bucharskaya; S. S. Pakhomiy; A. O. Efimova; G. N. Maslyakova (Исследования и практика в медицине)
Purpose of the study. The study's objective is to investigate the expression level of tissue and serum markers of oncogenesis and nephrofibrosis transforming growth factor beta (TGF‑β) and matrix metalloproteinase‑9 (MMP‑9) in patients operated for various stages of renal cell carcinoma.Materials and methods. The study prospectively included medical data of 60 patients with kidney cancer with T1–3N0M0 who received surgical treatment in the Clinic of Urologynamed after S. R. Mirotvortsev of the State Medical University from 2016 to 2019. The patients were divided into 3 groups: Group 1 included 20 patients who underwent laparoscopic kidney resection; Group 2–20 patients who underwent laparoscopic nephrectomy; Group 3–20 patients who underwent open nephrectomy. The control group consisted of 15 healthy volunteers without chronic kidney diseases. All patients signed an informed consent to participate in the study. All patients at the preoperative stage, in the early (7–10 days) and remote postoperative periods (after 1 and 2 years) were tested by solid‑phase ELISA on a StatFax 4200 analyzer using eBiosence and Cloud‑Clone Corp reagent kits for the serum concentration of oncogenesis markers MMP‑9 and TGF‑β1.Results. Initial increase of MMP‑9 concentration was detected in all groups of PCC patients compared to the control group (p ≤ 0.05). According to the results of ROC analysis, this indicator has high specificity and sensitivity for prognosis of preoperative stage of renal cell carcinoma. The sensitivity and specificity of MMP‑9 were 87.5 % and 62 %, respectively, and the diagnostically significant level of MMP‑9 was 958 ng/ml. A comprehensive analysis of the content of MMP‑9 and TGF‑β1 oncogenesis markers in serum and tumor cells revealed the correlation of these indicators in various biological objects.Conclusion. Markers of oncogenesis and nephrofibrosis TGF‑β1 and MMP‑9 provide an opportunity for non‑invasive monitoring of tumor progression and probability of metastasis in the clinical setting. Serum MMP‑9 are a reliable predictor of tumor growth. Serum TGF‑β1 concentration isn't a sufficiently reliable marker of tumor progression.